Prolonged Exposure to Platelet Activating Factor Transforms Breast Epithelial Cells - Chakravarty, Vaishali; Anandi, Libi; Ashiq, K. A.; Abhijith, K.; Umesh, Rintu; Lahiri, Mayurika (Frontiers in Genetics, 2021)
Lipid species are known to have various biological functions owing to their structural differences and each of them possesses a specific role to play depending upon their location and distribution in the cell. The level of lipid mediators is generally maintained in the cell by feedback mechanisms, however their improper degradation or enhanced production leads to their accumulation in the tumor microenvironment and disturbs the homeostasis of the cell. Platelet activating factor (PAF) is a known phospholipid mediator secreted upon immunological challenges by platelets, neutrophils, basophils and macrophages. PAF, as a potent inflammatory molecule, is well studied and its role in various cancers and cardiovascular diseases has also been investigated. Interestingly, increased levels of PAF have been found in blood plasma of smokers and breast cancer cells have shown accumulation of PAF in presence of cigarette smoke extract. This accumulation was found to increase tumor cell motility that in turn could promote metastasis. However, the effect of PAF on tumorigenesis has not yet been well explored. Here we show that continuous exposure of 3D breast acinar cultures to PAF resulted in activation of various oncogenic signaling pathways leading to transformation. We also found that presence of PAF in the micro-environment resulted in increased expression of PAF receptor (PAF-R), which corroborated with the higher expression of PAF-R detected in some epithelial cancers, as per literature. Thus, this study impresses on the fact that presence of PAF alters the cellular microenvironment and eventually triggers irreversible effects that can cumulatively lead to transformation.